Pengaruh Ekstrak Albumin Ikan Gabus (Chana striata) terhadap Kadar IFN-γ Pasien Tuberkulosis Paru dengan Pengobatan Fase Intensif (The Effect of Albumin Snakehead Fish (Chana striata) Extract on IFN-Y of Pulmonary Tuberculosis Patients during Intens - Henggar Allest Pratama; Erfan Efendi; Rini Riyanti (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Pulmonary tuberculosis is a respiratory infection disease caused by Mycobacterium tuberculosis infection in lung tissue. Mycobacterium tuberculosis could inhibit macrophage activation by inducing an increase of SOCS1 which can inhibit IFN-γ signaling process. Meanwhile, IFN-γ production continues as long as Mycobacterium tuberculosis still exist, so the IFN-γ levels stay high. This study aimed to investigate the effect of albumin snakehead fish (Chana striata) extract to decrease IFN-γ level. The study design was a quasy experimental design. The study subject was 24 tuberculosis patients during intensive phase medication, were divided into 2 groups. Experimental group was given 1500 mg/day albumin snakehead fish (Chana striata) extract while control group was placebo for 30 days. This study showed that albumin snakehead fish (Chana striata) extraxt can decrease significanly IFN-γ levels in the experimental group (p=0.006) but not statistically signicant if compared with the decrease of control group (p=0.061). It can be concluded that albumin snakehead fish (Chana striata) extract in dose of 1500 mg/day had not able to decrease IFN-γ levels of pulmonary tuberculosis patients during intensive phase medication yet. Keywords: tuberculosis, albumin, snakehead fish, IFN-γ